Enhancing Observation Report Writing through Differentiated Project-Based Learning with Real Objects and Motivation - Ogi Maya Sari; Tressyalina Tressyalina (AL-ISHLAH: Jurnal Pendidikan, 2025)
Writing observational reports poses challenges for vocational high school students, particularly in organizing factual information systematically. To address this issue, this study explores the effectiveness of a differentiated Project-Based Learning (PjBL) model assisted by real objects and moderated by students’ learning motivation. A quantitative experimental design with a 2×2 factorial structure was used. The population included all Grade X students at SMK Negeri 1 Padang Panjang (2024/2025), from which two comparable classes were purposively selected: X AKL1 (experimental group) and X AKL2 (control group). The experimental group was taught using a differentiated PjBL model with real objects, while the control group received conventional instruction. Instruments included a performance-based writing test and a Likert-scale motivation questionnaire. Data were analyzed using normality, homogeneity, t-tests, and two-way ANOVA in SPSS 25. The experimental group significantly outperformed the control group in writing observational reports (mean = 75.23 vs. 57.40; p 0.001). Among high-motivation students, the experimental group scored higher (84.11 vs. 81.00; p = 0.041), as did low-motivation students (67.44 vs. 56.56; p = 0.002). A significant interaction was found between the instructional model and learning motivation (Fₕ = 4.3238 Fₜ = 4.149). The findings indicate that integrating differentiated instruction, PjBL, and real objects can enhance students’ writing performance and motivation. This approach is especially effective in vocational education contexts, aligning with the Merdeka Curriculum’s emphasis on contextual, student-centered learning.